Increasing Leg Muscle Explosive Power Using Smith Machine Squat Training In Measured Sports - Dwinda Abi Permana; Dwi Kurnia Shandy (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to prove that there is a significant effect on leg muscle explosive power using smith machine squat training. In the study conducted using pre-experimental research with a pretest and posttest model on one group. The subjects of this study were male athletes of the KONI Kota Kediri measured sports with an age range of >17 years and a total of 20 athletes. This research process was carried out in 18 treatments/face-to-face meetings with a training frequency of 3 times per week for 6 weeks. The instrument used in this study was the standing broad jump test. In this study, the average result of the pretest was 2.0451 watts, then the average posttest was 2.210 watts. The data obtained from the pretest-posttest results were analyzed using statistical testing of the paired t-test. The results of the analysis of the paired t-test were 0.000 <0.05, which means that it can be concluded that there is a significant effect on increasing the explosive power of the leg muscles using the smith machine squat exercise.